The Entrepreneurship Development Center’s contribution to the student’s openness to the various components of the entrepreneurial ecosystem: The case of the Entrepreneurship Development Center at the University of Constantine 1 Frères Mentouri - RADJAH, Sabrina; BENNOUNE, Khireddine (Journal of Human Sciences, 2025)
This study seeks to elucidate the role of the Entrepreneurship Development Center in fostering entrepreneurial thinking among university students through its annual activities, as well as the impact of these activities on students’ engagement with the various elements of the entrepreneurial ecosystem. The research employs a descriptive approach for the theoretical framework and an analytical method for data evaluation. The study regarding the activities organized by the Entrepreneurship Development Center at Constantine 1 University for the years 2023 and 2024 concluded that the center’s offerings comprehensively address all components of the entrepreneurial ecosystem. This is achieved by engaging most stakeholders in student training and facilitating the establishment of their organizations, thereby reducing their inclination to pursue traditional employment, which they have been accustomed to for several years.